Schools and child antisocial behavior : in search for mediator effects of school-level disadvantage - Pauwels, Lieven (Sage open, 2015)
Contextual research on delinquency is primarily based on the idea that residential areas provide a major ecological setting that (indirectly) shapes observed differences in delinquency. Just like neighborhoods, schools differ in terms of their level of structural characteristics such as the concentration of immigrant children and children from disrupted families. Such characteristics may also shape delinquency. The present study aims to test the relationship between structural characteristics of schools and child antisocial behavior, using a sample of elementary school children (N = 779, aged 10-12 years in the urban context of Ghent, Belgium). This study found that the concentration of children from disrupted families has an independent effect on child delinquency, independent of social bonds, moral cognitions, and moral emotions. The contextual effect is fully mediated by exposure to peer delinquency